Multi-physical modeling and analysis on UAV launching system - Chin-Fa Lee; Jhy-Cherng Tsai; Cheng-Hsiung Kuo (Advances in Mechanical Engineering)
For UAVs unable to take off vertically, a launch device is essential, and accurate launch velocity prediction is crucial. This study develops two mathematical models for both the mechanical and the pneumatic subsystems of the launching system of unmanned aerial vehicles (UAVs) and solves these coupled, highly nonlinear ordinary differential equations by the fourth-order Runge-Kutta method. By applying this multi-physical model to the launching systems of UAVs, the trend with time of the shuttle displacement, velocity, and acceleration, as well as the tank and cylinder pressures in the mathematical results, are similar to those observed in real experiments. Using MATLAB as the platform, this multi-physical model accurately predicts the velocity of the launching system (or dummy), with a maximum error of 9.0% and a minimum error of 4.3% compared to the experimental results. Additionally, this multi-physical model reveals a linear relationship between the frictional force and pull force of the shuttle, which is consistent with the co-simulation results. Overall, these models not only offer the greatest design flexibility to understand and meet the required launching system’s performance, it will also save the cost and time for the efficient R&D procedure of future UAVs’ applications.